Kilka uwag na temat zeznań niewolników w procesie karnym - Loska, Elżbieta (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
In ancient Rome there was a rule that in the course of the trial the slave confession could not be used to the detriment of their owners. There have been exceptions to this rule since the time of the Republic, in the case of incest crime and conspiracy. A different approach to the use of the testimony of slaves was visible during the Principate. Laws, such as lex Iulia de adulteriis coërcendis, or imperial rescripts, provided for a number of possibilities to circumvent the republican ban, without actually breaking it, or abolishing it. Only in the case of crimen laese maiestatis it was explicitly allowed to torture the slaves in caput domini. During Dominate accepting the charges submitted by the slave against the owner was forbidden, excepting maiestas only. Accusing slave was punished with death.